How Do They Deal With Speaking Anxiety?: EFL Learners’ Strategies - Misnariah Idrus (Universitas Pendidikan Muhammadiyah (UNIMUDA) Sorong, 2023)
Emotion promotes various consequences on language learning (Maquidato, 2021). It includes language anxiety. (Brown 2000) defined language anxiety as the